Human YKT6 forms priming complex with STX17 and SNAP29 to facilitate autophagosome-lysosome fusion - Denghao Zheng; Mindan Tong; Shen Zhang; Yi Pan; Yanxiang Zhao; Qing Zhong; Xiaoxia Liu (Cell Reports, 2024)
Summary: Autophagy is crucial for degrading and recycling cellular components. Fusion between autophagosomes and lysosomes is pivotal, directing autophagic cargo to degradation. This process is driven by STX17-SNAP29-VAMP8 and STX7-SNAP29-YKT6 in mammalian cells. However, the interaction between STX17 and YKT6 and its significance remain to be revealed. In this study, we challenge the notion that STX17 and YKT6 function independently in autophagosome-lysosome fusion. YKT6, through its SNARE domain, forms a complex with STX17 and SNAP29 on autophagosomes, enhancing autophagy flux. VAMP8 displaces YKT6 from this complex, leading to the formation of the fusogenic complex STX17-SNAP29-VAMP8. We demonstrated that the YKT6-SNAP29-STX17 complex facilitates both lipid and content mixing driven by STX17-SNAP29-VAMP8, suggesting a priming role of YKT6 for efficient membrane fusion. Our results provide a potential regulation mechanism of autophagosome-lysosome fusion, highlighting the importance of YKT6 and its interactions with STX17 and SNAP29 in promoting autophagy flux.